Passiflora edulis: An Insight Into Current Researches on Phytochemistry and Pharmacology - He, Xirui; Luan, Fei; Yang, Yan; Wang, Ze; Zhao, Zefeng; Fang, Jiacheng; Wang, Min; Zuo, Manhua; Li, Yongsheng (Frontiers in Pharmacology, 2020)
Passion fruit (Passiflora edulis), a highly aromatic fruit and known as "the King of Fruits", is widely grown in tropical and subtropical areas of the world and becomes popular because of balanced nutrition and health benefits. P. edulis contain more than 119 phytochemical compounds and major bioactive components are polyphenol, flavonoids and polysaccharide. These components showed a wide range of health effects and biological activities such as antioxidant, anti-hypertensive, anti-tumor, antidiabetic, hypolipidemic activities, etc. Daily consumption of passion fruit at common doses seem non-toxic and safe. P. edulis has great potential development and the vast future application for this economically important crop worldwide, and it is in great demand as a fresh product or a formula for food, health care products or medicines. This mini-review provide systematically reorganized information on physiochemical features, nutritional benefits, biological activities, toxicity and potential applications of leaves, stems, fruits, and peels of P. edulis.